(untitled) (Experimental biology, 2016)
Results of studying of anatomo-morphological features of vegetative organs of Polygonum scabrum Moench, Polygonum amphibium L., Polygonum undulatum Murr. Comm. Gotting. and Polygonum minus Huds. Fl. Angl., having industrial quantities in the territory of the Republic of Kazakhstan are given in article. Results of qualitative component and quantitative composition of carbohydrates, coumarins, phenols, phenolic, amino- and fatty acids, anthraquinones and flavonoids on aboveground organs of plants are for the first time presented.